Measurement of Fluid Flow and Heat Transfer Performance in Rectangular Microchannel using Pure Water and Fe3O4-H2O Nanofluid - Che Sidik, Nor Azwadi; Abubakar, Saidu Bello; Yusof, Siti Nurul Akmal (Journal of Advanced Research in Applied Mechanics, 2020)
In this study, the three-dimensional rectangular silicon microchannel heat sink (MCHS) were analyzed numerically to investigate the fluid flow and heat transfer performance using pure water and Fe3O4-H2O as working fluids. The numerical method is based on finite volume method. CFD software’s involving GAMBIT and FLUENT were employed to perform the investigation numerically in the range of Reynolds number 140, 700 and 1400 and for volume fractions are in the range of ?=0.4, ?=0.6 and ?=0.8. It is observed that the presence of Fe3O4-H2O has effect of reducing the tempreture as particle volume fraction of Fe3O4-H2O increases due to its higher dynamic viscosity and lower heat capacity compared to pure water. The results show that the highest heat transfer enhancement is anticipated for Fe3O4-H2O with volume fraction of 0.8% due to higher thermal conductivity and Nusselt number. The Nusselt number Fe3O4-H2O increased with the increase of volume fraction and with the increase of Reynolds number. Overall, the simulated results showed that the heat transfer performance of Fe3O4-H2O with 0.8% was better than that of Fe3O4-H2O with 0.4%, of Fe3O4-H2O with 0.6%, and pure water. Increasing the thermal conductivity of working fluid enhanced the heat transfer performance of MCHS.